Innate and Adaptive Immunity in Calcific Aortic Valve Disease. (3rd May 2015) - Mathieu, Patrick; Bouchareb, Rihab; Boulanger, Marie-Chloé
Abstract : Calcific aortic valve disease (CAVD) is the most common heart valve disorder. CAVD is a chronic process characterized by a pathologic mineralization of valve leaflets. Ectopic mineralization of the aortic valve involves complex relationships with immunity. Studies have highlighted that both innate and adaptive immunity play a role in the development of CAVD. In this regard, accumulating evidence indicates that fibrocalcific remodelling of the aortic valve is associated with activation of the NF- κ B pathway. The expression of TNF- α and IL-6 is increased in human mineralized aortic valves and promotes an osteogenic program as well as the mineralization of valve interstitial cells (VICs), the main cellular component of the aortic valve. Different factors, including oxidized lipid species, activate the innate immune response through the Toll-like receptors. Moreover, VICs express 5-lipoxygenase and therefore produce leukotrienes, which may amplify the inflammatory response in the aortic valve. More recently, studies have emphasized that an adaptive immune response is triggered during CAVD. Herein, we are reviewing the link between the immune response and the development of CAVD and we have tried, whenever possible, to keep a translational approach.